IMPLEMENTASI PROFIL PELAJAR PANCASILA UNTUK MEMBENTUK KARAKTER PESERTA DIDIK KELAS V DI SDN 126 KOTA JAMBI - Dea Rina Hartati; Mita Sawitri; Nia Audina; Ria Apriani; Verra Gusniawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The Ministry of Education and Culture of the Republic of Indonesia has issued a new policy contained in Minister of Education and Culture Regulation No. 22 of 2020 concerning the Strategic Plan of the Ministry of Education and Culture for 2020-2024 related to the Pancasila Student Profile. This research aims to collect data regarding the application of the Pancasila Student Profile in shaping the character of students in class V of SDN 126/IV Jambi City. The research location was carried out at SDN 126/IV Jambi City using descriptive qualitative research methods. This research approach uses interviews, observation and documentation by testing the validity of the data through triangulation of data sources. Data analysis techniques include data collection, data reduction, data presentation, and drawing data conclusions. The research results show that the implementation of the Pancasila Student Profile in shaping the character of students in class V of SDN 126/IV Jambi City has gone well. The formation of the Pancasila Student Profile is carried out both through intra-curricular and extra-curricular activities. In the formal curriculum, the dimensions of the Pancasila Student Profile are integrated into teaching and learning activities (KBM), both inside and outside the classroom. Meanwhile, in extra-curricular activities, the formation of the Pancasila Student Profile is integrated through activities that have implemented these dimensions. Obstacles faced in forming the Pancasila Student Profile include lack of student attention and lack of communication and collaboration. The proposed solution to overcome these obstacles is to increase communication and collaboration and involve all relevant parties.